2011
DOI: 10.1016/j.envpol.2011.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, speciation and availability of antimony (Sb) in soils and terrestrial plants from an active Sb mining area

Abstract: a b s t r a c tHere, we present one of the first studies investigating the mobility, solubility and the speciationdependent in-situ bioaccumulation of antimony (Sb)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(113 citation statements)
references
References 47 publications
8
89
3
1
Order By: Relevance
“…Several plants in this study exhibited a high ability to accumulate Sb in their tissues, particularly in their roots, such as D. erythrosora at site S3, F. dibotrys (D. Don) at site S7, Rumex patientia L. at site S2, Oplismenus undulatifolius(A) Bea at site S4 and P. vittata at site S8. Boehmeria nivea has reportedly accumulated levels of Sb as high as 5579 mg/kg in its roots at XKS (Okkenhaug et al, 2011). In this study, however, such levels were not observed, which may reflect the great variation in plant accumulations of Sb from site to site.…”
Section: Accumulation Of As and Sb By Plants At Xkscontrasting
confidence: 54%
See 1 more Smart Citation
“…Several plants in this study exhibited a high ability to accumulate Sb in their tissues, particularly in their roots, such as D. erythrosora at site S3, F. dibotrys (D. Don) at site S7, Rumex patientia L. at site S2, Oplismenus undulatifolius(A) Bea at site S4 and P. vittata at site S8. Boehmeria nivea has reportedly accumulated levels of Sb as high as 5579 mg/kg in its roots at XKS (Okkenhaug et al, 2011). In this study, however, such levels were not observed, which may reflect the great variation in plant accumulations of Sb from site to site.…”
Section: Accumulation Of As and Sb By Plants At Xkscontrasting
confidence: 54%
“…For example, biomethylation of Sb by the filamentous fungus Scopulariopsis brevicaulis was recently established (Jenkins et al, 1998). Nevertheless, the information on organic species of Sb in plants had rarely been reported, with most current studies on Sb speciation in plants only focusing on Sb V and Sb III (Okkenhaug et al, 2011). Müller et al used a chromatographic method to study the Sb speciation in Pteris vittata L. spiked with 16 mg/kg Sb V , they found that Sb V , Sb III , trimethylated Sb V and an unidentified Sb compound in the plant (Muller et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sorption of Sb V to Fe (hydr)oxides is known to decrease with increasing pH above pH 7, but this can explain only a very small part of the observed increase in Sb V that occurred parallel with the release of Mn in the nonsterilised columns. [19] Other abiotic processes that have also been suggested in the literature to mobilise Sb, such as ratelimited desorption of Sb V from Fe (hydr)oxides, [22] chemical dissolution of Sb-bearing phases [7,39] or competitive desorption, [40] do not provide plausible explanations for the difference in Sb release at the initial stages of the experiment between columns with and without sterilisation treatment, although they may have contributed to the release of Sb that occurred independent of these treatments. Although no consumption of lactate by soil microbial communities was found before flow interruption in the sterilised column (Supplementary material, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these factors are interlinked and, for example, drainage and pH are particularly important with respect to redox cycling of Fe. Iron oxides are major natural sorbents for Sb (Johnson et al, 2005;Mitsunobu et al, 2006Mitsunobu et al, , 2010Wilson et al, 2010;Okkenhaug et al, 2011), and Filella et al (2002b) noted the importance of Fe (oxy)hydroxides in limiting Sb mobility, particularly in acidic soils typical of those found at the Glendinning site. As in many upland areas of the UK, the soils are also organic-rich and previous work has shown that Sb, As and Pb bind to organic matter to varying extents (e.g.…”
Section: Introductionmentioning
confidence: 99%